Metabolomic Study on Tridacna maxima Giant Clams Reveals Metabolic Fingerprint of Environmental Pollutants - Almulhim, Fatimah; Rossbach, Susann; Emwas, Abdul-Hamid; Kharbatia, Najeh M.; Jaremko, Lukasz; Jaremko, Mariusz; Duarte, Carlos M. (Frontiers in Marine Science, 2022)
Metabolite profiling of marine invertebrates, such as bivalve mollusks, may not only provide insights into the health state of an individual holobiont, but also the pollution levels of their environment Here, we combined 1H nuclear magnetic responance (NMR) spectroscopy and mass spectrometry (MS)-based metabolomics techniques to investigate the organ-specific metabolomic profiles of Tridacna maxima giant clams. Clams were collected from across-shelf gradient in the Red Sea, from inshore to off-shore. We unequivocally profiled 306 metabolites and observed that the sampling location had minimal effects on metabolite composition. However, we observed significant differences in metabolite profiles among different organs (i.e., gills, mantle organ, and digestive system). Importantly, in addition to endogenous metabolites, we detected the presence of terephthalic acid and isophthalic acid, which likely originate from marine plastic ingestion. Collectively, our study opens opportunities for a deeper understanding of Tridacna maxima physiology through metabolomics, and illustrates the power of invertebrate metabolite profiling for monitoring plastic-related aquatic pollutants.